Pembuatan Stimuli ASMR (Autonomous Sensory Meridian Response) pada Animasi Pengenalan Makanan Tradisional Indonesia - Yuly, Ade Rahma (MULTINETICS, 2022)
Pandemic conditions with government regulations to avoid crowds and travel restrictions force the public to stay at home, especially urban communities that cannot visit other regions. The application of ASMR stimuli in animated the introduction of traditional Indonesian food can invite the viewer to feel a more profound atmosphere by adding a trigger to the sense of hearing through an audio enhancement to produce a suitable response for their eyes seen. The method used in this study is efficient DDD-E (decide-design-evaluation) in audio enhancement for ASMR stimuli in an animated production. The four phases of the DDDE method are in sequence and concise, so it is suitable for producing audio on multimedia products. The study results in the form of animation with audio enhancement quality to obtain ASMR stimuli (autonomous sensory meridian response), so the viewer becomes more engaged with the appearance of animated recognition of traditional cuisine. Animation displays the introduction process, cooking processes, and presentation that supports the atmosphere will be added with the audio enhancement technology.